ANALYSIS OF TRI HITA KARANA'S TEACHINGS WITH STORYING METHOD TO IMPROVE CHARACTER IN EARLY CHILDREN IN LEARNING HINDU RELIGION - I Gede Raka Mudana (STAH Dharma Sentana Sulawesi Tengah, 2023)
Character education is an effort to develop personality values ​​based on a nation's view of life which is reflected through cultural values ​​and characters that grow in a nation. Advances in technology have had a major impact on aspects of life, especially education. The development of this technology must be accompanied by character education because it is very important to be taught from the level of early childhood education, because this is a good start to shape the future generation of a nation to grow and develop. One of the effective methods used in developing the character values ​​of Tri Hita Karana in early childhood is to use the storytelling method. This article uses a qualitative method with a literature study approach related to instilling the values ​​of Tri Hita Karana in early childhood. The application of the teachings of Tri Hita Karana from an early age is also important because in early childhood the brain experiences the fastest development phase. The brain will retain any experience or information that is most frequently repeated and discard those that take place only once and without high emotional context. To understand the analysis of character education based on Tri Hita Karana, the author describes starting from the cultivation of character education values ​​at the early childhood education level and the analysis process of Tri Hita Karana at the early childhood education level.